Heat stress relief by tidally driven cold‐water bores on a coral reef atoll - Kelly Boden‐Hawes; Nicole L. Jones; Matthew D. Rayson; James P. Gilmour; Taryn Foster (Limnology and Oceanography, 2026)
Understanding how physical transport mechanisms influence coral reef temperature dynamics is crucial for effective management. Typically, sea surface temperature (SST) is used to estimate coral heat stress, yet subsurface physical processes can significantly influence reef temperature dynamics and are imperative to consider in predictive efforts. Using observations and a 3D numerical model, we conducted a volume‐based temperature budget analysis to investigate heat distribution at south Scott Reef, an atoll on the Australian North West Shelf. We identified how tidally driven processes influence the reef's heat budget by quantifying the volume flux of different temperature classes through each entrance. We found during the spring‐tide local, tidally driven cold‐water bores transported water ~ 2°C cooler than background through northwestern entrances of the lagoon semidiurnally leading to a net increase in cooler water. Coral surveys taken over the 2016 marine heatwave show sites exposed to the bores experienced a 0–10% reduction in coral cover compared to 10–60% in other regions. Using a dividing streamline model between January–May 1998–2022, we estimated water > 6°C cooler than recorded SST was delivered to the lagoon (40 m BSL) twice daily when tidally driven bores were active, that is, spring‐tide periods. Temperature differences between the surface and subsurface remained